SWOT ANALYSIS IN SALES STRATEGY AT THE COFFEE SHOP IN THE PANDEMIC ERA (Study of Belikopi Coffee Shop in Nganjuk) - Unpapar, Aldrich Alfatera (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
During the pandemic, several coffee shops in Nganjuk city were unable to operate due to the manager's inability to maintain their business amidst the increasingly uncertain challenges of the pandemic. But not with the Belikopi Nganjuk coffee shop which actually opened or grand opening its outlet in Nganjuk in a pandemic situation (December 19, 2020), and has survived until now. The purpose of this study is important to find out the general description of the Belikopi Nganjuk strategy that has been carried out to attract the attention of visitors. In addition, the purpose of this research is also to formulate alternative sales strategies for Belikopi Nganjuk in the future so that they can compete superiorly and can apply the right sales strategy. This study uses 2 analytical methods, namely marketing mix analysis and SWOT analysis (Strength, Weakness, Opportunity, and Threat) at Belikopi Nganjuk. From the SWOT analysis data through the IFE (Internal Factor Evaluation) matrix which describes the company's strengths and weaknesses, the EFE (External Factor Evaluation) matrix which explains the opportunity and threat factors, and the quadrant diagram showing Belikopi Nganjuk's current position, it was found that the highest weight score for strength is 0.85, the highest weight for weakness is 0.425, the highest weight for opportunity is 0.65, and lastly, the highest weight for the highest threat is 0.325. Furthermore, the total value of the IFE matrix is 3.035 and the EFE matrix is 3.18, thus placing Belikopi Nganjuk in quadrant I of the SWOT analysis quadrant diagram Keywords: Coffe Shop, SWOT analysis, Sales Strategies, Belikopi Nganjuk.